Team Synchronization and Individual Contributions in Coop-Space Fortress. (December 2020) - Li, Huao; Ni, Tianwei; Agrawal, Siddharth; Hughes, Dana; Sycara, Katia
This work studied human teamwork with a concentration on the influence of team synchronization and in- dividual differences on performance. Human participants were paired to complete collaborative tasks in a simulated game environment, in which they were assigned roles with corresponding responsibilities. Cross- correlation analysis was employed to quantify the degree of team synchronization and time-lag between two teammates' collective actions. Results showed that team performance is determined by factors at both the individual and team levels. We found interaction effects between team synchronization and individual differences and quantified their contributions to team performance. The application of our research findings and proposed quantitative methods for developing adaptive agents for human-autonomy teaming is discussed.